Case report: First manifestation of multiple sclerosis temporally correlated with COVID-19 vaccination - Czarnowska, Agata; Kapica-Topczewska, Katarzyna; Tarasów, Eugeniusz; Tarasiuk, Joanna; Chorąży, Monika; Kochanowicz, Jan; Kułakowska, Alina (Frontiers in Neurology, 2023)
There are several case reports describing a temporal correlation between the first clinical manifestation of multiple sclerosis (MS) and the occurrence of relapses with vaccination against SARS-CoV-2. Here we report a case of a 33-year-old male who developed partial right upper and lower extremities numbness 2 weeks after receiving Johnson & Johnson’s Janssen COVID-19 vaccine. The brain MRI performed during diagnostics in the Department of Neurology detected several demyelinating lesions, one with enhancement. Oligoclonal bands were present in the cerebrospinal fluid. The patient was treated with high-dose glucocorticoid therapy with improvement and the diagnosis of MS was made. It seems plausible that the vaccination revealed the underlying autoimmune condition. Cases like the one we reported here are rare, and – based on current knowledge – the benefits of vaccination against SARS-CoV-2 far outweigh the potential risks.